PENERAPAN PEMBELAJARAN BERBASIS MEDIA GAMBAR SERI UNTUK MENINGKATKAN KEAKTIFAN MATERI MENGARANG KELAS III - Nur Hayati Nur (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
This study aims to describe the learning process using a series of media images that can improve the activity and learning outcomes of Indonesian students in class III SD Negeri Rejoyoso in the academic year 2018/2019. This type of research is classroom action research. The design of this study refers to the design of classroom action research according to Kemmis and Mc Taggart. The results showed that the use of a media image series can increase the activity and student learning outcomes. The average overall student activeness in cycle I was 87% and increased student activeness to 89.2% in cycle II. Based on the results of the study it can be concluded that the use of series image media can increase the activeness of students in Indonesian subjects class III Elementary School 02 Rejoyoso Bantur 2018/2019 Academic Year. Keywords: Student activeness, media image series